The Critical Issues of Knowledge Sharing in E-Government Initiative. - Ibrahim, Othman; Abdullah, Nurfarahin Jasmine See (2006)
E-government aims at exploiting Information and Communication Technologies (ICT) to provide better quality services to citizens and business, mainly through electronic delivery channels. E-government will encompass the entire spectrum of government operations, impacting citizen to government, business to government and government to government transactions. With the E-government issues there the need of knowledge management to apply in it. Knowledge management (KM) has changed from one generation to the next through constant improvements and new perspectives. Knowledge management in e-government are still in an early state of evolution and it is only recently that researchers decided to intensify their efforts in these fields. The knowledge of e-government that has evolved different froms of e-government services and applications is not properly organized and used, it will be lost in antiquity. Therefore taking steps to both save the knowledge gained from the evolution of e-government history and the tools to sure it can be accessed and used by a multitude of stakeholders. One of the element in knowledge management is knowledge sharing. This paper present knowledge management in e-government discussing the key issues related to operational of human in knowledge sharing among staff to staff and staff to customer. Researcher suggest for the research methodology which are combination of qualitative and quantitative method. An approach for this research is conceptual model and framework of knowledge sharing.